Educational Administration at Cluster III State Elementary Schools Basarang District, Kapuas Regency - Noorhasanah; Irawanto; Riky Welly Saputra; Muhammad Jamili (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to: (1) analyze the administration of education at Gugus III Public Elementary School, Basarang District, Kapuas Regency, (2) identify the driving and inhibiting factors in improving the quality of education administration at Gugus III Public Elementary School, Basarang District, Kapuas Regency, (3) know the solution in improving the quality of education administration in Gugus III State Elementary School, Basarang District, Kapuas Regency. The type of research used in this research is descriptive. The data collected comes from interviews (Interviews), observation, and documentation. Data analysis in qualitative research The results showed: (1) The administration of education at Gugus III State Elementary School, Basarang District, Kapuas Regency, still needed to run optimally (2) Meanwhile, the obstacles faced in the implementation of educational administration were the inadequate quantity of teaching staff. (3) Solutions in improving the quality of education administration.